Metagenomics Reveals Microbial Diversity and Metabolic Potentials of Seawater and Surface Sediment From a Hadal Biosphere at the Yap Trench - Zhang, Xinxu; Xu, Wei; Liu, Yang; Cai, Mingwei; Luo, Zhuhua; Li, Meng (Frontiers in Microbiology, 2018)
Hadal biosphere represents the deepest part of the ocean with water depth greater than 6,000 m. Accumulating evidence suggests the existence of unique microbial communities dominated by heterotrophic processes in this environment. However, investigations of the microbial diversity and their metabolic potentials are limited because of technical constraints for sample collection. Here, we provide a detailed metagenomic analysis of 3 seawater (5,000-6,000 mbsl) and 3 surface sediments (4,435-6,578 mbsl) from a hadal biosphere at the Yap Trench of the western Pacific. Distinct microbial community compositions were observed in seawater and sediment samples, with the dominance of Gammaproteobacteria and Thaumarchaeota, respectively. Comparative analysis of the genes involved in carbon, nitrogen and sulfur metabolisms revealed that heterotrophic processes (i.e., degradation of carbohydrates, hydrocarbons, and aromatics) are the most common microbial metabolisms in the seawater, while chemolithoautotrophic metabolisms such as ammonia oxidation with the HP/HB cycle for CO2 fixation probably dominated the surface sediment communities of the Yap Trench. Furthermore, abundant genes involved in stress response and metal resistance were both detected in the seawater and sediments, thus the enrichment of metal resistance genes is further hypothesized as characteristic of the hadal microbial communities. Overall, this study sheds light on the metabolic versatility of microorganisms in the Yap Trench, their roles in carbon, nitrogen, and sulfur biogeochemical cycles, and how they have adapted to this unique hadal environment.